Meandering to Recovery : Post-Nargis Social Impacts Monitoring Ten Years After - Kostner, Markus; Han, Min Min; Pursch, Samuel (World Bank, Washington, DC, 2018)
On May 2, 2008, Cyclone Nargis struck Myanmar’s Ayeyarwady Delta and swept across the region toward Yangon. By the time the storm had passed, it had killed over 140,000 people, tearing apart families, destroying homes, and shattering livelihoods. In the months and years following Nargis,communities, supported by the national and international aid community, worked to rebuild their lives and repair the devastation that the cyclone had caused. Homes were rebuilt, paddy field walls repaired, and new fishing boats purchased. However, even as the process of recovery inched forward, villagers have had to contend with new and diverse shocks and changes that have both enabled and slowed their efforts to rebuild. Among others, climate change has led to unpredictable weather, hampering livelihoods, while the migration boom to Yangon and elsewhere has provided economic opportunity even as it has altered the local social fabric. These more recent issues have had a complex inter-relationship with changes wrought by Nargis. As time has passed, they have become the primary concern of most villages studied by the social impacts monitoring (SIM) research. But the long-term effects of Nargis remain visible, combining with newer issues to create new challenges,exacerbate old problems, and, in some cases, even hasten the recovery process. By focusing on a panel of 40 Nargis-affected villages across time, five rounds of SIM have been able to track how village life has changed both post-Nargis and, in more recent years, as villagers faced both new challenges and continued recovery from Nargis. This fifth round of SIM (SIM 5) provides a snapshot of village economic and social life in 2017 and analyzes change over more than nine years since Nargis. It assesses three main areas: (i) This focus area examines the conditions of livelihoods and the local socioeconomy in the context of Nargis’ destruction and the evolving context of the rural economy across Myanmar over the past five years. It looks at the three main livelihood groups (farmers, fishers, and landless laborers) and at key issues such as debt, land, and housing and local infrastructure; (ii) This area assesses how communities have dealt with both the long-term social upheaval caused by Nargis and the more recent (but no less dramatic) changes that have accompanied Myanmar’s political and economic transition; (iii) New to this round of SIM, the final analytical focus area identifies what recovery and resilience mean for households and communities in the Ayeyarwady Delta, what factors are most important in the recovery process and in building resilience, and to what extent villagers have had and have the capacity to develop both; SIM 5 placed particular emphasis on understanding change over time, both since 2013 (when the SIM 4 research was conducted) and prior to Cyclone Nargis. As much as possible, SIM 5 draws causal links between exogenous events (such as cyclones, other natural disasters, political change, and national economic development) and household and community actions.